The influence of friends and siblings on the physical activity and screen viewing behaviours of children aged 5–6 years: a qualitative analysis of parent interviews. Issue 5 (14th May 2015) - Edwards, M J; Jago, R; Sebire, S J; Kesten, J M; Pool, L; Thompson, J L
Abstract : Objectives: The present study uses qualitative data to explore parental perceptions of how their young child's screen viewing and physical activity behaviours are influenced by their child's friends and siblings. Design: Telephone interviews were conducted with parents of year 1 children (age 5–6 years). Interviews considered parental views on a variety of issues related to their child's screen viewing and physical activity behaviours, including the influence that their child's friends and siblings have over such behaviours. Interviews were transcribed verbatim and analysed using deductive content analysis. Data were organised using a categorisation matrix developed by the research team. Coding and theme generation was iterative and refined throughout. Data were entered into and coded within N-Vivo. Setting: Parents were recruited through 57 primary schools located in Bristol and the surrounding area that took part in the B-ProAct1v study. Participants: Fifty-three parents of children aged 5–6 years. Results: Parents believe that their child's screen viewing and physical activity behaviours are influenced by their child's siblings and friends. Friends are considered to have a greater influence over the structured physical activities a child asks to participate in, whereas the influence of siblings is more strongly perceived over informal and spontaneous physical activities. In terms of screen viewing, parents suggest that their child's friends can heavily influence the content their child wishes to consume, however, siblings have a more direct and tangible influence over what a child watches. Conclusions: Friends and siblings influence young children's physical activity and screen viewing behaviours. Child-focused physical activity and screen viewing interventions should consider the important influence that siblings and friends have over these behaviours.